Prevalence, predictors, and patient-reported outcomes of long COVID in hospitalized and non-hospitalized patients from the city of São Paulo, Brazil - Malheiro, Daniel Tavares; Bernardez-Pereira, Sabrina; Parreira, Kauê Capellato Junqueira; Pagliuso, João Gabriel Dias; de Paula Gomes, Emerson; de Mesquita Escobosa, Daisa; de Araújo, Carolina Ivo; Pimenta, Beatriz Silva; Lin, Vivian; de Almeida, Silvana Maria; Tuma, Paula; Laselva, Claudia Regina; et al. (Frontiers in Public Health, 2024)
Background Robust data comparing long COVID in hospitalized and non-hospitalized patients in middle-income countries are limited. Methods A retrospective cohort study was conducted in Brazil, including hospitalized and non-hospitalized patients. Long COVID was diagnosed at 90-day follow-up using WHO criteria. Demographic and clinical information, including the depression screening scale (PHQ-2) at day 30, was compared between the groups. If the PHQ-2 score is 3 or greater, major depressive disorder is likely. Logistic regression analysis identified predictors and protective factors for long COVID. Results A total of 291 hospitalized and 1,118 non-hospitalized patients with COVID-19 were included. The prevalence of long COVID was 47.1% and 49.5%, respectively. Multivariable logistic regression showed female sex (odds ratio [OR] = 4.50, 95% confidence interval (CI) 2.51–8.37), hypertension (OR = 2.90, 95% CI 1.52–5.69), PHQ-2 > 3 (OR = 6.50, 95% CI 1.68–33.4) and corticosteroid use during hospital stay (OR = 2.43, 95% CI 1.20–5.04) as predictors of long COVID in hospitalized patients, while female sex (OR = 2.52, 95% CI 1.95–3.27) and PHQ-2 > 3 (OR = 3.88, 95% CI 2.52–6.16) were predictors in non-hospitalized patients. Conclusion Long COVID was prevalent in both groups. Positive depression screening at day 30 post-infection can predict long COVID. Early screening of depression helps health staff to identify patients at a higher risk of long COVID, allowing an early diagnosis of the condition.